BPAP: FPGA Design of a RISC-like Processor for Elliptic Curve Cryptography Using Task-Level Parallel Programming in High-Level Synthesis - Ifrim, Rares; Popescu, Decebal (Cryptography, 2025)
Popular technologies such as blockchain and zero-knowledge proof, which have already entered the enterprise space, heavily use cryptography as the core of their protocol stack. One of the most used systems in this regard is Elliptic Curve Cryptography, precisely the point multiplication operation, which provides the security assumption for all applications that use this system. As this operation is computationally intensive, one solution is to offload it to specialized accelerators to provide better throughput and increased efficiency. In this paper, we explore the use of Field Programmable Gate Arrays (FPGAs) and the High-Level Synthesis framework of AMD Vitis in designing an elliptic curve point arithmetic unit (point adder) for the secp256k1 curve. We show how task-level parallel programming and data streaming are used in designing a RISC processor-like architecture to provide pipeline parallelism and increase the throughput of the point adder unit. We also show how to efficiently use the proposed processor architecture by designing a point multiplication scheduler capable of scheduling multiple batches of elliptic curve points to utilize the point adder unit efficiently. Finally, we evaluate our design on an AMD-Xilinx Alveo-family FPGA and show that our point arithmetic processor has better throughput and frequency than related work.